The Influence Of Physical And Non-Physical Work Environment On Work Ethic Among Civil Servants At The Department Of Population And Civil Registration In Landak Regency - Ilis, Kristina; Ahmadia, Eru (UNIVERSITAS PAKUAN, 2024)
This study investigates the effect of physical and non-physical work environment on the work ethic of civil servants at the Population and Civil Registration Office of Landak Regency. As technology advances and workplace dynamics change, the environment in which people work becomes increasingly important to their effectiveness. This study sought to examine how elements such as workplace layout, lighting, equipment, and interpersonal dynamics between coworkers and superiors can affect motivation and work ethic. Data were collected from 39 government workers through questionnaires and then analyzed using multiple linear regression using SPSS 25. The results showed that the physical environment had a substantial positive influence on work ethic (β = 0.327, p 0.05), implying that an aesthetically pleasing office is essential in enhancing work motivation. However, the non-physical environment, including human relations and organizational culture, had no significant effect (β = 0.031, p 0.05). This suggests that while a good workplace culture is important, it may not directly influence work ethic as much as a pleasant and well-functioning physical environment. This research suggests that improving physical working conditions is a strategic method to improve employee performance. Further research could focus on other factors, such as leadership style or job satisfaction, which may also contribute to building a strong work ethic.